2019
DOI: 10.1182/blood-2019-123164
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability in Patients with Multiple Myeloma Treated with Daratumumab: A Systematic Review and Meta-Analysis of Phase III Randomized Controlled Trials

Abstract: Introduction: Multiple myeloma, which accounts for 1% of all cancers, is a hematologic cancer in which clonal plasma-cell proliferation leads to complications and death. Over the recent years, it has shown that the introduction of novel agents, including daratumumab and the incorporation of proteasome inhibitors and immunomodulatory drugs has improved outcomes in patients with multiple myeloma. Daratumumab is a human, CD38-targeting, IgG1κ monoclonal antibody with direct antitumor effects and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In fact, as regards infectious diseases, the FAERS suggests a significant association between daratumumab-based regimens and multiple opportunistic infections [4] and pivotal randomized phase 3 clinical trials documented that the rates of infectious complications, in particular respiratory tract infections including viral complications, are higher in the anti-CD38 mAbs combination with IMiDs or PIs plus dexamethasone group than IMiDs or PIs and dexamethasone alone. In the same line, a recent metanalysis of clinical trials [39], pooling five randomized phase 3 studies (ALCYONE, MAIA, CASSIOPEIA, CASTOR and POLLUX), confirmed that the incidence of TD due to infection/pneumonia was slightly higher with daratumumab than in the control group (0.95% vs 0.73%); conversely, the rates of TD due to treatment-emergent adverse events (TEAEs) (6.77% vs 10.08%) and treatment-related deaths (3.61% vs 4.34%) were significantly lower in the daratumumab group than in the control arm. In contrast to anti-CD38 mAbs, the addition of elotuzumab with IMiDs did not result in a higher incidence of treatment-related neutropenia and pneumonia [36][37][38].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, as regards infectious diseases, the FAERS suggests a significant association between daratumumab-based regimens and multiple opportunistic infections [4] and pivotal randomized phase 3 clinical trials documented that the rates of infectious complications, in particular respiratory tract infections including viral complications, are higher in the anti-CD38 mAbs combination with IMiDs or PIs plus dexamethasone group than IMiDs or PIs and dexamethasone alone. In the same line, a recent metanalysis of clinical trials [39], pooling five randomized phase 3 studies (ALCYONE, MAIA, CASSIOPEIA, CASTOR and POLLUX), confirmed that the incidence of TD due to infection/pneumonia was slightly higher with daratumumab than in the control group (0.95% vs 0.73%); conversely, the rates of TD due to treatment-emergent adverse events (TEAEs) (6.77% vs 10.08%) and treatment-related deaths (3.61% vs 4.34%) were significantly lower in the daratumumab group than in the control arm. In contrast to anti-CD38 mAbs, the addition of elotuzumab with IMiDs did not result in a higher incidence of treatment-related neutropenia and pneumonia [36][37][38].…”
Section: Discussionmentioning
confidence: 96%
“…Despite these clinical observations, to analyze the severity and outcomes of infectious disease with daratumumab vs comparators, some questions need to be asked. Firstly, it is very interesting to observe that, although grade ≥3 infections (25.7% vs 19.0%) and pneumonia (9.3% s 5.7%) [5] were reported more frequently in the anti-CD38 mAbs group than in the control group, the incidence of serious AEs and the incidence of infections leading to death were similar compared with control arms [39]. The safety profile of quadruplet regimens is similar to those of triplet regimens and there is no evidence of additional significant toxicities [6,[9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 98%